The potential of highly sensitive persons in leadership roles: Strengths, challenges, and implications for organizational behavior and leadership practice - Leonie Sophie Schmidt; Malte Martensen (IU Internationale Hochschule, 2026)
Sensory Processing Sensitivity (SPS) describes individual differences in how strongly people respond to sensory and emotional information in their environment. Individuals high in SPS are often referred to as Highly Sensitive Persons (HSPs) and tend to be more susceptible to both supportive and unsupportive environments. SPS is associated with greater depth of processing, emotional reactivity, sensitivity to subtle stimuli, and susceptibility to overstimulation. To examine how this trait relates to leadership, this study explored the experiences of seven HSPs through qualitative semi-structured interviews and interpreted the data with reflexive thematic analysis. Three themes were constructed: (1) SPS as a leadership resource, (2) navigating misaligned leadership norms, and (3) experience, understanding, and regulating SPS in leadership. The findings provide insights into how HSPs perceive and manage sensitivity in leadership roles and suggest that SPS may function as a leadership resource when supported by favorable environmental conditions, self-acceptance, and effective coping strategies. This research contributes to the emerging literature on SPS in leadership and highlights the need for greater awareness and organizational support for highly sensitive leaders.
Keywords: M12; D91; M14; 650; Sensory Processing Sensitivity; Highly Sensitive Person; Leadership Experiences; Differential Susceptibility; Coping Strategies